Repeated Exposure to Conditioned Fear Stress Increases Anxiety and Delays Sleep Recovery Following Exposure to an Acute Traumatic Stressor - Greenwood, Benjamin N.; Thompson, Robert S.; Opp, Mark R.; Fleshner, Monika (Frontiers in Psychiatry, 2014)
Repeated stressor exposure can sensitize physiological responses to novel stressors and facilitate the development of stress-related psychiatric disorders including anxiety. Disruptions in diurnal rhythms of sleep-wake behavior accompany stress-related psychiatric disorders and could contribute to their development. Complex stressors that include fear-eliciting stimuli can be a component of repeated stress experienced by humans, but whether exposure to repeated fear can prime the development of anxiety and sleep disturbances is unknown. In the current study, adult male F344 rats were exposed to either control conditions or repeated contextual fear conditioning for 22 days followed by exposure to either no, mild (10), or severe (100) acute uncontrollable tail shock stress. Exposure to acute stress produced anxiety-like behavior as measured by a reduction in juvenile social exploration and exaggerated shock-elicited freezing in a novel context. Prior exposure to repeated fear enhanced anxiety-like behavior as measured by shock-elicited freezing, but did not alter social exploratory behavior. The potentiation of anxiety produced by prior repeated fear was temporary; exaggerated fear was present 1 day but not 4 days following acute stress. Interestingly, exposure to acute stress reduced REM and NREM sleep during the hours immediately following acute stress. This initial reduction in sleep was followed by robust REM rebound and diurnal rhythm flattening of sleep / wake behavior. Prior repeated fear extended the acute stress-induced REM and NREM sleep loss, impaired REM rebound, and prolonged the flattening of the diurnal rhythm of NREM sleep following acute stressor exposure. These data suggest that impaired recovery of sleep / wake behavior following acute stress could contribute to the mechanisms by which a history of prior repeated stress increases vulnerability to subsequent novel stressors and stress-related disorders.